Pengaruh Dimensi Kualitas Pelayanan Puskesmas S. Parman Banjarmasin Terhadap Kepuasan Pasien Dalam Memperoleh Pelayanan Kesehatan - Widi Utami; Ahmad Alim Bachri (JWM (JURNAL WAWASAN MANAJEMEN), 2013)
This study aims to identify and analyze quality of service (as variable indefendent) are services, personnel skills, health care costs, availability of drugs, and environmental security effect on patient satisfaction (as a variable defendant) in the public health services in health centers S.Parman Banjarmasin. The research was conducted in March until May 2012, using a random survey of 100 respondents from the community in the Kecamatan Pasar Lama and surrounding Antasan Besar and enjoy the health center at a public patient, patient’s health insurance and public health insurance. The results of this study indicate that the quality of service is service, personnel skills, health care costs, availability of drugs, and environmental safety and simultaneous partial effect on patient satisfaction. All variables indefendent positive and significant impact on patient satisfaction and the availability of drugs is the most significant variable impact because the main objective to restore the patient’s health. Satisfaction index S.Parman community health center Banjarmasin judged by the standards of quality of service is considered appropriate.